Toluene Exposure Concentration and Neurotoxic Risk Quotient among Industrial Workers in Surabaya: A Cross-Sectional Study - Suardi Zurimi; Abdul Rohim Tualeka (Poltekita: Jurnal Ilmu Kesehatan, 2025)
Background: Toluene poses significant health hazards to humans. Occupational exposure among workers who use toluene as a solvent may lead to various adverse health effects, including dizziness, vertigo, ocular and skin irritation, respiratory disturbances, as well as disorders of the liver, kidneys, and central nervous system. This study aimed to examine the association between toluene concentration and non-carcinogenic risk characteristics with neurotoxic effects across five industrial settings in the Surabaya region. Methods: This observational study employed a cross-sectional design and was conducted in five industries in Surabaya that utilize toluene as a solvent in their production processes, located in Osowilangun, Ketintang, Jemursari, Kalijudan, and AUP Which will be implemented in 2025. The study population consisted of 90 workers exposed to toluene, of whom 77 participants were selected using an accidental sampling technique. The variables examined included toluene concentration, toluene risk quotient (RQ), and neurotoxic effects. Results: Overall, 50 workers (65%) had unsafe risk quotient (RQ) levels, and 48 workers (62.3%) experienced neurotoxic effects. Although the majority of workers (52.0%) were exposed to toluene concentrations below the threshold limit value, those exposed to concentrations above the threshold had a 1.38-fold higher risk of neurotoxic effects, and workers with unsafe RQ had a 1.4-fold increased risk compared with those with safe RQ. Statistical analysis showed no significant association between toluene concentration or RQ and neurotoxic effects (p > 0.05). Conclusion: Although not statistically significant, the study suggests that the Risk Quotient (RQ) of toluene is a key determinant of neurotoxic risk, highlighting the importance of monitoring and controlling exposure in the workplace.